2019
DOI: 10.35940/ijrte.b2462.078219
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Blockchain Technology in Education System

Abstract: The Blockchain for Education platform helps us to make the tamper-proof certificates and their correct and the overall permanent allocation of these certificates to learners, as well as verification of certificates. It can reduce the overall frauds and tampering of the degrees and certificates. Blockchain technology can be used to solve many educational problems and can help educators as well as learners to monitor the learning outcomes. The data can be stored securely and tamper proof format when it’s stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…In the Table 6 presents the manuscripts obtained from the literature review and subsequently describes the contribution of the papers according to the identified areas. [17] Accreditation of knowledge 12 Implementation of blockchain technology in education system [11] Fraud of grade 13 Blockchain and the Future of Digital Learning Credential Assessment and Management [10] Accreditation of knowledge 14 EduCTX: A blockchain-based higher education credit platform [18] Accreditation of knowledge…”
Section: Resultsmentioning
confidence: 99%
“…In the Table 6 presents the manuscripts obtained from the literature review and subsequently describes the contribution of the papers according to the identified areas. [17] Accreditation of knowledge 12 Implementation of blockchain technology in education system [11] Fraud of grade 13 Blockchain and the Future of Digital Learning Credential Assessment and Management [10] Accreditation of knowledge 14 EduCTX: A blockchain-based higher education credit platform [18] Accreditation of knowledge…”
Section: Resultsmentioning
confidence: 99%
“…Blockchain verifies every transaction through a consensus mechanism between nodes ensuring no single party has the unique power to alter it. As soon as a new block of data is verified and introduced in the chain, it is almost impossible to modify or remove this [68]. Additionally, the decentralised characteristic of blockchain is fundamental for guaranteeing the integrity of information.…”
Section: ) Benefitsmentioning
confidence: 99%
“…Cantidad Artículos relacionados Certificación 5 (Franzoni et al, 2019;Karale & Khanuja, 2019;Kuppusamy, 2019;LuxTag, 2019;Sharma, 2018) Pasaporte de Aprendizaje 6 (Gräther et al, 2018;Jirgensons & Kapenieks, 2018;Mikroyannidis et al, 2019;Ocheja et al, 2019;Tapscott & Kaplan, 2019;Wanotayapitak et al, 2019) Identidad Soberana 4 (Alsayed Kassem et al, 2019;Bai et al, 2019;Sahmim et al, 2019;Zhu & Badr, 2018) Otros 4 (Bessa & Martins, 2019;Mao et al, 2019;Rahman et al, 2018;Turkanović et al, 2018) Tabla 1 -Soluciones de la tecnología Blockchain…”
Section: Soluciones Bc En La Educaciónunclassified